2016
DOI: 10.1021/acs.jpcb.6b02332
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Defects Induced by Melittin in Model Lipid Membranes: A Solution Atomic Force Microscopy Study

Abstract: Quantitative characterization of membrane defects (pores) is important for elucidating molecular basis of many membrane active peptides. We study kinetic defects induced by melittin in vesicular and planar lipid bilayers. Fluorescence spectroscopy measurements indicate that melittin induces time-dependent calcein leakage. Solution atomic force microscopy (AFM) is used to visualize melittin induced membrane defects. After initial equilibration, the most probable defect radius is ~3.8 nm in 1,2-dilauroyl-sn-glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 61 publications
(135 reference statements)
5
37
2
Order By: Relevance
“…2B) [28, 30, 54]. For 0.1 μM melittin, almost no increase of the fluorescence signal is observed over the 30-min incubation period; the increase of the fluorescence signal becomes fairly significant over ~30 min for 0.2 μM melittin; near full leakage is achieved within a few minutes for melittin ≥0.3 μM.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2B) [28, 30, 54]. For 0.1 μM melittin, almost no increase of the fluorescence signal is observed over the 30-min incubation period; the increase of the fluorescence signal becomes fairly significant over ~30 min for 0.2 μM melittin; near full leakage is achieved within a few minutes for melittin ≥0.3 μM.…”
Section: Resultsmentioning
confidence: 99%
“…To support this statement, we expose a POPC/POPG bilayer to the well-studied antimicrobial peptide melittin, which is known to form transmembrane pores (or defects) [28, 54, 58]. After equilibrating with 0.4 μM melittin for ~30 min, the bilayer is perforated with numerous pore-like defects (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They also observed that adding an N-terminal myc-tag to the htt exon1 fragments can prevent the interaction of htt with the bilayer. The interaction between melittin, a 26-residue amphipathic peptide, and lipid membranes has been studied using in situ AFM by Pan et al [159]. Their results showed that melittin induced defects in lipid bilayers, which can be delayed by introducing cholesterol.…”
Section: Lipidmentioning
confidence: 99%